2018
DOI: 10.1186/s12978-018-0635-z
|View full text |Cite
|
Sign up to set email alerts
|

Does short message service improve focused antenatal care visit and skilled birth attendance? A systematic review and meta-analysis of randomized clinical trials

Abstract: BackgroundIn low resource circumstances, non-adherence for available health services is a major cause of inefficiency in health care delivery. MHealth has been projected as a possible solution to support women during pregnancy, birth and puerperium period, to increase the uptake of essential maternal services.ObjectivesThis systematic review and meta-analysis study was aimed to determine the effectiveness of short message services (SMS)on Focused Antenatal Care (FANC) visits and the attendance of skilled birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 48 publications
5
58
0
Order By: Relevance
“…Similarly, SMS reminders may be effective for promoting antenatal care visits. In a systematic review and meta‐analysis, pregnant women who received text messaging were more likely to complete the four, focused antenatal care visits previously recommended by the WHO (OR: 2.74, 95% CI: 1.41 to 5.32) [107]. National programmes have begun to integrate such strategies into routine antenatal care [108].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, SMS reminders may be effective for promoting antenatal care visits. In a systematic review and meta‐analysis, pregnant women who received text messaging were more likely to complete the four, focused antenatal care visits previously recommended by the WHO (OR: 2.74, 95% CI: 1.41 to 5.32) [107]. National programmes have begun to integrate such strategies into routine antenatal care [108].…”
Section: Resultsmentioning
confidence: 99%
“…This report continues to demonstrate that only 53% of women with no education attended the recommended for antenatal visits compared to 72% of women with more than a secondary education. Though not meant for illiterates, a recent systematic review demonstrates some evidence that mobile phone-based SMS text reminders can improve adherence to attending antenatal visits [27] in a low resource setting. Being reminded by mobile phone-SMS based reminders could potentially result into forming a habit of adopting a health behavior [28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in Malawi and Iraq found increased ANC attendance among women who received a unidirectional text or voice messaging intervention and access to hotlines or phone numbers to call with questions [ 5 , 6 ]. A recent meta-analysis of seven RCTs in low- and middle-income countries found evidence that text messages for pregnant women significantly increased ANC attendance by 174% [ 7 ]. Other studies have also found SMS text messaging interventions to increase mothers’ knowledge, preparedness, feelings of empowerment, and satisfaction with ANC [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of seven RCTs in low- and middle-income countries found evidence that text messages for pregnant women significantly increased ANC attendance by 174% [ 7 ]. Other studies have also found SMS text messaging interventions to increase mothers’ knowledge, preparedness, feelings of empowerment, and satisfaction with ANC [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%